2018
DOI: 10.1083/jcb.201711055
|View full text |Cite
|
Sign up to set email alerts
|

PI(4,5)P2 determines the threshold of mechanical force–induced B cell activation

Abstract: B lymphocytes use B cell receptors (BCRs) to sense the chemical and physical features of antigens. The activation of isotype-switched IgG-BCR by mechanical force exhibits a distinct sensitivity and threshold in comparison with IgM-BCR. However, molecular mechanisms governing these differences remain to be identified. In this study, we report that the low threshold of IgG-BCR activation by mechanical force is highly dependent on tethering of the cytoplasmic tail of the IgG-BCR heavy chain (IgG-tail) to the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 79 publications
2
31
0
Order By: Relevance
“…The basic residues in the IgG tail interact with PI(4,5)P2 at the PM, and abrogation of this interaction through mutation of the basic residues lead to dissociation of from the PM, albeit without evident spontaneous signaling . Basic residue mutations also reduced the enrichment between PI(4,5)P2 and the IgG‐BCR microdomains and reduction of PI(4,5)P2 at the PM through enzymatic manipulation confirmed that the interaction between the IgG‐BCR CT and PI(4,5)P2 is required for the low mechanical force threshold observed for the activation of the IgG‐BCR . The lower sensitivity of IgG isotype‐switched memory B cells to force due to electrostatic interactions between IgG basic residues and PI(4,5)P2 reveals how memory B cells show fast antigen recall responses.…”
Section: Electrostatic Interaction‐driven Immune Receptor Signalingmentioning
confidence: 71%
See 3 more Smart Citations
“…The basic residues in the IgG tail interact with PI(4,5)P2 at the PM, and abrogation of this interaction through mutation of the basic residues lead to dissociation of from the PM, albeit without evident spontaneous signaling . Basic residue mutations also reduced the enrichment between PI(4,5)P2 and the IgG‐BCR microdomains and reduction of PI(4,5)P2 at the PM through enzymatic manipulation confirmed that the interaction between the IgG‐BCR CT and PI(4,5)P2 is required for the low mechanical force threshold observed for the activation of the IgG‐BCR . The lower sensitivity of IgG isotype‐switched memory B cells to force due to electrostatic interactions between IgG basic residues and PI(4,5)P2 reveals how memory B cells show fast antigen recall responses.…”
Section: Electrostatic Interaction‐driven Immune Receptor Signalingmentioning
confidence: 71%
“…While the IgM cytoplasmic tail of the BCR is very short and is not implicated in BCR signaling, the mouse IgG‐BCR cytoplasmic tail contains membrane‐proximal basic residues and is highly hydrophobic, and recruits Grb2 when ligand bound (Figure ) . FRET studies have shown that the IgG cytoplasmic tail is associated to the PM in resting B cells through electrostatic interactions provided by the membrane‐proximal basic as well as hydrophobic residues . In quiescent B cells, IgG‐BCR membrane microdomains are specifically enriched in PI(4,5)P2, while PI(3,4,5)P3, PS and PA are neither enriched nor depleted but may also provide charge for PM binding .…”
Section: Electrostatic Interaction‐driven Lipid Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…4) adds in vivo support to a growing list of anionic lipids that set force sensing thresholds. For example, PIP2 sets the threshold for mechanical B-cell activation 59 . Likewise, sphingosine-1-phosphate (S1P), an anionic lipid similar to PA, regulates pain in mice 60 .…”
Section: Disruptionmentioning
confidence: 99%